2020
DOI: 10.3390/ma13041018
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Vanadium Oxide Addition on the Physicochemical Performance Stability and Intercalation of Lithium Ions of the TiO2-rGO-electrode in Lithium Ion Batteries

Abstract: This work determines the effect of the addition of various amounts of vanadium oxide on the work of a cell built from a hybrid VxOy-TiO2-rGO system in a lithium-ion cell. Moreover, a new method based on solvothermal chemistry is proposed for the creation of a new type of composite material combining reduced graphene, vanadium oxide and crystalline anatase. The satisfactory electrochemical properties of VxOy-TiO2-rGO hybrids can be attributed to the perfect matching of the morphology and structure of VxOy-TiO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Lithium metal generally exhibits a higher surface area, providing more sites for lithium ions to interact with the electrolyte and engage in electrochemical reactions. In contrast, the presence of lithium ions within the Gr structure reduces the effective surface area and restricts the available active sites, resulting in a lower capacity for Li‐Gr [50] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium metal generally exhibits a higher surface area, providing more sites for lithium ions to interact with the electrolyte and engage in electrochemical reactions. In contrast, the presence of lithium ions within the Gr structure reduces the effective surface area and restricts the available active sites, resulting in a lower capacity for Li‐Gr [50] …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the presence of lithium ions within the Gr structure reduces the effective surface area and restricts the available active sites, resulting in a lower capacity for Li-Gr. [50] Moreover, when comparing the Li-G and Li-Gr anodes at the same rate (Figure 5b), it is evident that the Li-G anode exhibits a capacity of only 750 mAh g À 1 , which is significantly lower than that of the Li-Gr anode. The capacity of Li-Gr/G falls in between the two.…”
Section: Electrode Morphology and Surface Areamentioning
confidence: 95%
“…Because of those limitations, graphene is only examined as a hybrid or nanocomposite compound or in modified form. However, it is well known that graphene could be also used as a conductive carrier and connect the active materials because of its highly good mechanical properties, thus preventing the destruction of electrode structure [ 40 ]. The three-dimensional (3D) conductive network (formed by graphene) may improve the electron and ion movement within the electrode materials [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, because of its excellent mechanical properties, graphene can also be used as a conductive carrier and to connect active materials, preventing the destruction of electrode structures [63]. Graphene-based three-dimensional (3D) conductive networks may improve electron and ion movement within electrode materials [64]. Several studies have reported the use of reduced graphene oxide (rGO) as a hybrid component with other metal oxides; for example, an NiO/SnO 2 /rGO composite has been employed as an anode for Na-ion and Li-ion batteries, which showed a specific capacity as high as 800 mAh g −1 at a current density of 1000 mA g −1 , even after 400 cycles [65].…”
Section: Carbon-based Electrodesmentioning
confidence: 99%